Application of Preparing Financial Reports for Micro, Small and Medium Enterprises Based on Entity Accounting Standards Without Public Accountability (SAK ETAP) - Tania Tania; Erna Hendrawati; Lilik Pirmaningsih (International Journal of Economics, Management and Accounting, 2024)
Financial Accounting Standards for Entities Without Public Accountability are standards for preparing financial reports for MSMEs with the aim of making it easier for creditors and investors to view financial reports so that MSMEs can get loans to increase capital and make their business more advanced. The implementation of the preparation of financial statements by UD. X is not in accordance with the financial statements based on SAK ETAP. The purpose of this study is to find out (1) What are the obstacles faced by UD. X in compiling financial reports based on SAK ETAP (2) What are the impacts of not compiling financial reports based on SAK ETAP (3) Implementation of financial statement preparation at UD. X. This research uses qualitative method with case study method. The techniques used for data collection are interviews, observation, and documentation. The results of this study are (1) Lack of human resources so that they cannot prepare financial reports properly and correctly (2) Owners do not understand the importance of financial statements properly so they cannot make the right decisions (3) Recording of financial statements is recorded simply, not yet based on SAK ETAP.